A Systematic Review on the Effects of Different Types of Probiotics in Animal Alzheimer's Disease Studies - de Rijke, Tanja J.; Doting, M. H. Edwina; van Hemert, Saskia; De Deyn, Peter P.; van Munster, Barbara C.; Harmsen, Hermie J. M.; Sommer, Iris E. C. (Frontiers in Psychiatry, 2022)
Alzheimer’s disease (AD) is a global public health priority as with ageing populations, its prevalence is expected to rise even further in the future. The brain and gut are in close communication through immunological, nervous and hormonal routes, and therefore, probiotics are examined as an option to influence AD hallmarks, such as plaques, tangles, and low grade inflammation. This study aimed to provide an overview of the available animal evidence on the effect of different probiotics on gut microbiota composition, short chain fatty acids (SCFAs), inflammatory markers, Amyloid-β (Aβ), and cognitive functioning in AD animal models. A systematic literature search was performed in PubMed, SCOPUS, and APA PsychInfo. Articles were included up to May 2021. Inclusion criteria included a controlled animal study on probiotic supplementation and at least one of the abovementioned outcome variables. Of the eighteen studies, most were conducted in AD male mice models (n=9). Probiotics of the genera Lactobacillus and Bifidobacterium were used most frequently. Probiotic administration increased species richness and/or bacterial richness in the gut microbiota, increased SCFAs levels, reduced inflammatory markers, and improved cognitive functioning in AD models in multiple studies. The effect of probiotic administration on Aβ remains ambiguous. B. longum (NK46), C. butyricum, and the mixture SLAB51 are the most promising probiotics, as positive improvements were found on almost all outcomes. The results of this animal review underline the potential of probiotic therapy as a treatment option in AD.